Analisis Teras Berita pada Surat Kabar Harian Tribun Pekanbaru - Helsy Arides Hanyuli; Muhammad Mukhlis (UIR Press, 2023)
The research method used was that this research was carried out in Pekanbaru in 2020. Furthermore, this research method used a qualitative descriptive method with the aim of describing the writing style of news headlines in the headlines of the Pekanbaru Tribune newspaper which were found in the research as is. The term